Study on groundwater abstraction by horizontal drains for minimization of saltwater upconing from below - Hoang, Nguyen Van; Cong, Nguyen Thanh; Hai, Quach Quang; Quang, Tran Van (Vietnam Journal of Earth Sciences, 2018)
In many places in Vietnam central region, the fresh coastal sand dune aquifers have an interface with salty water below, so upon groundwater (GW) abstraction, there is a risk of salty water upconing to the abstraction facilities. With the same abstraction rate, the horizontal drains shall significantly reduce the groundwater level (GWL) drawdown, which significantly reduces the development of saltwater upconing. The results analysis for the design of groundwater abstraction facilities in Thach Tri commune, Thach Ha district, Ha Tinh province have shown the effectiveness of the solution. For infinite distributed aquifers, the GWL drawdown in the facility area with the abstraction rate of 100m3/day by eight 4m- and 8m-long horizontal drains is from 11.7% to 16.8% lower in comparison to a vertical well, respectively, (GWL drawdown in vertical well is 0.733m, GWL drawdown in center of 4m-long horizontal drains is 0.646m and in 8m-long horizontal drains is 0.603m). For 1km x 1km aquifer bounded by no-flow boundaries, GWL drawdown in the vertical well and in the center of eight 4m-and 8m-long horizontal drains are 2.313m, 1.293m and 1.255m, respectively. This is corresponding to GWL drawdown decrease of 44.1% and 45.7% in comparison to the vertical well. The significantly reduced GWL drawdown in abstraction facilities of horizontal drains will significantly reduce the level of salty water upconing and therefore increase the time of abstraction of fresh water. References CPEO, 2010. Updated 2010 tech tree list of summary cleanup technology descriptions: Horizontal Wells. http://www.cpeo.org/techtree/ttdescript/horzwel.htm Dagan, G. and Bear, J., 1968. Solving the problem of local interface upconing in a coastal aquifer by the method of small perturbations. J. Hydr. Res., 6, 15-44. Diersch,H.-J. Prochnow D. and Thiele M., 1984. Finite-element analysis of dispersion-affected saltwater upconing below a pumping well. Appl. Math. Modelling, 8, 305-312. Falkovich G., 2011. Fluid Mechanics. Cambridge University Press, 167p. Fletcher G. Driscoll, 1987. Groundwater and Wells. Published by Johnson Division, St. Paul, Minnesota 55112, USA, 1089p. Kushtanova G.G., 2015. Well test analysis. Kazan University, 31p. https://doi.org/10.15625/0866-7187/38/2/8603. Marta Faneca Sanchez, Khairul Bashar, Gijs Janssen, Gualbert Dude Essink, Marjolein Vogels, Jan Snel, Yangxiao Zhou and Roelof Stuurman, 2015. SWIBANGLA: Managing salt water intrusion impacts in coastal groundwater systems of Bangladesh. Deltares, The Netherlands UNESCO-IHE, The Netherlands Jahangirnagar University, Bangladesh, 153p. https://doi.org/10.15625/0866-7187/39/1/9231. Nguyen Ngoc Quynh, 2012. Determination of required geometric sizes of sand dunes for their stability in the Central Plains from Quang Ngai province to Binh Thuan province. Journal of Water Resources Science and Technology, 9, 2-6. Nguyen Tien Hai, Tran Nghi, Nguyen Van Bach, 2004. Formation characteristics and evolution of coastal strips of sands in Quang Binh. Journal of Geology, ISSN 0866-7381. Series A, 281, 30-40. Nguyen Van Dan, Vo Cong Nghiep, Dang Huu On, 1996. Groundwater of the North Trung Bo coastal plains. Geological Survey of Vietnam, 86p. Nguyen Xuan Truong, Nguyen The Tiep, 1998. Sea terrace in Vietnam with corresponding geological formations. Journal of Science 1. Hanoi University, 69-76. Phan Van Truong, 2015. Hydrogeochemistry characteristics and salinity of groundwater in Quaternary sediments in the coastal zone of Ha Tinh province. J. Sci. of the Earth, 37(1), 70-78. https://doi.org/10.15625/0866-7187/37/1/6557. Pieter S. Pauw Sjoerd E.A.T.M. van der Zee Anton Leijnse Gualbert H.P. Oude Essink, 2015. Saltwater Upconing Due to Cyclic Pumping by Horizontal Wells in Freshwater Lenses. J. Ground Water, 54(4), 521-531. https://doi.org/10.1111/gwat.12382. Soylu M. E., Istanbulluoglu E., Lenters J. D. and T. Wang, 2011. Quantifying the impact of groundwater depth on evapotranspiration in a semi-arid grassland region. Hydrol. Earth Syst. Sci., 15, 787-806,. www.hydrol-earth-syst-sci.net/15/787/2011/doi:10.5194/hess-15-787-2011. Truong Minh Duc, 2015. Climate change and environment in the Central coastal plain. Journal Vietnam Social Sciences, 89, 34-45.